Exploiting Signaling Pathways and Immune Targets Beyond the Standard of Care for Ewing Sarcoma - Casey, Dana L.; Lin, Tsung-Yi; Cheung, Nai-Kong V. (Frontiers in Oncology, 2019)
Ewing sarcoma (ES) family of tumors includes bone and soft tissue tumors that are often characterized by a specific translocation between chromosome 11 and 22, resulting in the EWS-FLI1 fusion gene. With the advent of multi-modality treatment including cytotoxic chemotherapy, surgery, and radiation therapy, the prognosis for patients with ES has substantially improved. However, a therapeutic plateau is now reached for both localized and metastatic disease over the last two decades. Burdened by the toxicity limits associated with the current frontline systemic therapy, there is an urgent need for novel targeted therapeutic strategies. In this review, we discuss the current treatment paradigm of ES, and explore preclinical evidence and emerging treatments directed at tumor signaling pathways and immune targets.